INTI International University Campus (INTI-IU) Security Monitoring System With Face Recognition Technology - Yap, Choi Sen; Yew, Zheng Han; Chong, Fong Kim (INTI International University, 2020)
The study is based on the stealing case happened at INTI International University Campus (INTI-IU) where student lost their personal belongings such as laptop, bag, smartphone, and wallet in the campus. When the case was reported, the INTI-IU security department has referred to the closed-circuit television (CCTV) records to trace the suspect but the footage was too grainy to make out the person’s identity. The tracing process is time-consuming and not effective, and always ended with unclosed cases. The author is proposing a campus security monitory system with face recognition technology to identify the unauthorized person who has entered the campus illegally. Once the stranger is identified, the security department will be alert immediately for further action. This will tighten the security on campus and provide a safer place for the staff and students.